Glochidium Metamorphosis in the Endangered Freshwater Mussel Margaritifera auricularia (Spengler, 1793): A Histological and Scanning Electron Microscopy Study - Araujo, Rafael; Cámara, Nicolás; Ramos, M. Ángeles (Journal of Morphology, 2002)
7 páginas, 4 figuras The metamorphosis of the glochidiumof the critically endangered Margaritifera auricularia in the gills of a host is studied here for the first time. Siberian sturgeon, Acipenser baeri, were infected with glochidia and regularly inspected using scanning and optical microscopy. The mature glochidia immediately attach to the epithelium of the sturgeon gill filaments, piercing the secondary lamellae and the connective tissues, blood cells, and vessels within the lamellae. Once the epithelium is pierced, overlapping host lamellae cover the glochidium and form a cyst. Metamorphosis takes place inside the cyst. Sixteen days after infection the glochidium becomes spherical in shape and the larval muscle is reabsorbed. The two adductor muscles of the juvenile are observed 34 days after infection at 16–20°C. Metamorphosis is complete in approximately 51 days at 18–22°C and in 65 days at 16–17°C. Released juveniles have a spherical shell with a thin rim of new shell material and a finely ciliated foot. Juvenile mean measurements are: length 190 m, width 193 m, and height 210 m. J. Morphol. 254: 259–265, 2002. © 2002 Wiley-Liss, Inc. Demografía, hábitat y ciclo vital de Margaritifera auricularia and the Fauna Ibérica Project (DGES PB95-0235) Peer reviewed